Optimizing Computer-Based Learning in the 21st Century in Karawang - Asyari, Lutfi; Lisnawati, Lisnawati; Rahman, Muklis; Sofi, Thea Anetha; Ruhiat, Neng Elsa Novianti; Firmansyah, Cecep (Fakultas Kewirausahaan Universitas Garut, 2023)
The use of project-based and problem-based learning methods, which prioritize the application of technology in learning, is increasingly recognized as an effective approach. The descriptive method used in this community service program is designed to provide a clear and systematic overview of the implementation and outcomes of activities aimed at improving technology competency among educators. The first step in this community service program is identifying problems related to the low level of optimization of computer-based learning in Karawang. By using this descriptive method, the community service program in Karawang is expected to bring about significant changes in the implementation of computer-based learning and improve teacher competency. The results of this community service program demonstrate the effectiveness of innovative teaching methods, such as the use of digital technology in learning. Overall, this community service program has not only successfully improved teacher skills but also paved the way for broader implementation of technology-based education in Karawang.